The cattle feeding industry of Kansas - P. Phar (Kansas Agricultural Experiment Station Research Reports, 1968)
The Kansas cattle feeding industry has grown tremendously since 1956. The 1968 January Cattle on Feed Report shows more than ten times as many cattle in commercial feedlots as in 1956. Farm feedlots have also increased, but since 1966 over 50 percent of our cattle have been fed in lots with at least 1,000 head capacity.
Keywords: Cattlemen& #x27; s Day; 1968; Report of progress (Kansas State University. Agricultural Experiment Station); 518; Beef; Commercial feedlots; Farm feedlots; Grain